2008
DOI: 10.1097/mao.0b013e31817f7382
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Superior Semicircular Canal Dehiscence on the Labyrinth

Abstract: The relationship found between the superior canal dehiscence size and the stimulator frequency has clinical implications in the diagnosis and management of patients with SSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 13 publications
4
22
0
1
Order By: Relevance
“…This is due to the starting point of the dehiscence being closer to the OW for Case V than for the other cases. Previous studies (Rajan et al, 2008; Songer and Rosowski, 2007) showed that, at low frequencies, a larger dehiscence up to the cross-sectional area of the SC caused a larger decrease in the hearing threshold for AC stimulation, while it caused a larger increase in the hearing threshold for BC stimulation. In addition, Songer and Rosowski (2010) proposed that a shorter distance between the input window (OW) and the dehiscence increases the hearing threshold for AC stimulation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is due to the starting point of the dehiscence being closer to the OW for Case V than for the other cases. Previous studies (Rajan et al, 2008; Songer and Rosowski, 2007) showed that, at low frequencies, a larger dehiscence up to the cross-sectional area of the SC caused a larger decrease in the hearing threshold for AC stimulation, while it caused a larger increase in the hearing threshold for BC stimulation. In addition, Songer and Rosowski (2010) proposed that a shorter distance between the input window (OW) and the dehiscence increases the hearing threshold for AC stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…But it also decreases the bone-conducted (BC) threshold, producing an improvement in BC hearing at low frequencies, which has not been well understood. Recently, the relationship between the hearing threshold and the dehiscence size (or location) has been studied in order to elucidate the mechanisms of SSCD syndrome and develop ways of screening patients for SSCD (Rajan et al, 2008; Songer and Rosowski, 2010; Niesten et al, 2012). Large air-bone gaps (ABGs) were shown to accompany SSCDs at low frequencies through animal experiments (fat sand rat and chinchilla).…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7,9,11,12,19,21,22 Pfammater et al noted that a larger dehiscence correlated with vestibulocochlear manifestations, while other studies found no associations. 5-7,9,11 And though Niesten et al did not find any correlation between dehiscence length and clinical signs and symptoms, when they grouped patients together based on their symptom profile, patients with auditory symptoms had significantly longer dehiscences starting closer to the ampulla compared to those without auditory complaints.…”
Section: Discussionmentioning
confidence: 96%
“…Rajan et al found that with longer dehiscences, lower stimuli frequencies were required to provoke a nystagmic response during electronystagmography. 19 In addition, several groups have reported significant correlations between longer dehiscences and lowered cVEMP thresholds. 5,11 As for cVEMP and oVEMP amplitudes, there are conflicting reports regarding the correlation between dehiscence size and amplitudes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study the same authors found no correlation between dehiscence size and auditory symptoms [10]. An approximate correlation between the size of the canal dehiscence and the threshold at which a vestibular response was triggered has been reported [58]. However, these researchers used a linear measurement of a curved defect that can lead to significant inaccuracies.…”
Section: Why Does Dehiscence Occur?mentioning
confidence: 92%